Study of the features of the formation and accumulation of UDMH and NDMA in plants (Journal of Geography and Environmental Management, 2019)
The article provides a brief overview of current trends in studying the environmental impact of rocket and space activity. The effect of rocket fuel is disclosed, where the main toxicants are UDMH and its transformation products: nitrosodimethylamine, dimethylamine, tetramethyltetrazene. The entry of rocket fuel components into the environment contributes to the formation of local biochemical surface anomalies. The results of studies on the behavior of rocket fuel components in the natural landscapes of the areas of falling of separated rocket carrier parts are considered. The results on the formation and accumulation of UDMH and NDMA by plants at the sites of accidental crashes of launch vehicles, with the results of a quantitative chemical analysis of samples of plants and soils, are summarized.The work shows that in the soil at the places of emergency falls of the pH the contamination with the products of the decomposition of UDMH, including NDMA, persists for a long time. There is a periodic appearance of NDMA in plants in the absence of NDMG and NDMA in the soil, re-contamination of the soil and vegetation cover of NDMG and NDMA after their absence for several years is also noted, while the area of contamination of vegetation cover is tens of times higher than the area of identified soil contamination by the RFC and their transformation productsIt has been established that the formation and accumulation of UDMH by plants at the sites of SP LV fallings depends on a number of factors: on the season of the year (humidity, temperature), on the family of plants, on the geochemical conditions of their habitats, on the proximity of sources of intake of UDMH, and that UDMH can be stored in plants, at the places of heptyl spills at the level of regional pollution for more than ten years.
Keywords: симметриялы емес диметилгидразин; нитрозодиметиламин; ракеталы-космосты іс әрекет; ракетаның жанар жағар майы; топырақтың ластануы; НДМГ және НДМА түзілуі және жинақталуы